Fullerene coated indium tin oxide counter electrode of Prussian blue electrode for enhanced electrochromic properties - Lee, Kyuha; Kim, A-Young; Lee, Joong Kee (ELSEVIER SCIENCE BV, 2015)
Fullerene coated ITO electrodes were prepared by a vacuum thermal evaporation system where fullerene (C-60) powders were used as a deposition source. The fullerene coated electrodes act as an ion storage layer for electrochromic devices (ECDs). The ECDs are comprised of Prussian blue (PB) electrodes as the EC electrode, fullerene coated ITO electrodes as the counter electrode, and an electrolyte containing LiClO4 salt. By employing fullerene coated ITO electrodes, the lower transmittance in the colored state (T-c) was achieved because of the lower transmittance of fullerene coated ITO. It led to an increase in the change in optical density (ACID) according to the increase in the thickness of the fullerene films. Also, the charge density per electrode area (Q(d)) of the ECDs increased with the increase in the thickness of the fullerene films. This result indicates that the amounts of lithium ions and PB molecules, which are used for the EC phenomenon, were increased. As a result, EC properties such as the ADD and response time were enhanced by employing fullerene coated ITO electrodes because fullerene films provided the ion storage layer as the counter electrode of the PB electrode. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: FILMS; SPECTROSCOPY